SAE Technical Paper Series 1998
DOI: 10.4271/980787
|View full text |Cite
|
Sign up to set email alerts
|

Supercharged Homogeneous Charge Compression Ignition

Abstract: The Homogeneous Charge Compression Ignition (HCCI) is the third alternative for combustion in the reciprocating engine. Here, a homogeneous charge is used as in a spark ignited engine, but the charge is compressed to auto-ignition as in a diesel. The main difference compared with the Spark Ignition (SI) engine is the lack of flame propagation and hence the independence from turbulence. Compared with the diesel engine, HCCI has a homogeneous charge and hence no problems associated with soot and NO X formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(157 citation statements)
references
References 16 publications
4
150
1
2
Order By: Relevance
“…[12][13][14][15][16][17] The most common clean-combustion techniques under consideration are homogeneous charge compression ignition (HCCI) and lowtemperature combustion (LTC); both involve modifications to the air-fuel mixture, ignition timing, air charge boost pressures, and percentage of exhaust gas recirculation (EGR) in the charge air. The goal of each of these technologies is to improve the engine thermal efficiency while minimizing unwanted exhaust compounds such as NO x and particulate matter (PM/soot).…”
Section: Powertrain Materialsmentioning
confidence: 99%
“…[12][13][14][15][16][17] The most common clean-combustion techniques under consideration are homogeneous charge compression ignition (HCCI) and lowtemperature combustion (LTC); both involve modifications to the air-fuel mixture, ignition timing, air charge boost pressures, and percentage of exhaust gas recirculation (EGR) in the charge air. The goal of each of these technologies is to improve the engine thermal efficiency while minimizing unwanted exhaust compounds such as NO x and particulate matter (PM/soot).…”
Section: Powertrain Materialsmentioning
confidence: 99%
“…Results from simulations of n-heptane and iso-octane with CAI combustion [29], cited in Figures 1 and 2, confirmed that both fuels ignited (main ignition) when air and fuel mixture reached a temperature of 1100K. Results from experimental studies on CAI combustion [1][2][3][4][5][6][7][8][9][10][11][12][13][30][31][32][33][34][35][36][37][38][39][40][41][42][43] proved the consistency of this temperature and its independence from fuel type. Figure 2.…”
Section: Fundamentals Of Cai Combustionmentioning
confidence: 70%
“…As a result, high peak pressure accompanied with a high rate of heat release and knock related problems could occur if rich mixtures were used [33][34][35][40][41][42]. CO and HC emissions from CAI combustion could be higher than conventional CI [41] and SI [33] engines, too.…”
Section: Licensed To Loughborough Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…This expression is obtained from the experimental results (Christensen et al 1998). The characteristics of the engine and the natural gas fuel used in the analysis are given in Table 5.…”
Section: Multi-cylinder Engine Set-point Optimizationmentioning
confidence: 99%